23 EMERGENT COLECTOMY RATES DECREASED WHILE ELECTIVE IPAA RATES WERE STABLE OVER TIME: A NATIONWIDE INPATIENT SAMPLE STUDY. (18th January 2018) - Ungaro, Ryan; Saha, Aparna; Poojary, Priti; Paramsothy, Sudarshan; Hirten, Robert; Cohen, Louis; Gallinger, Zane; Oikonomou, Ioannis; Mehandru, Saurabh; Cho, Judy; Greenstein, Alex; Nadkarni, Girish; et al.
Abstract: Background: Despite advances in medical therapy for UC, many patients still need surgery. Data on UC colectomy rates in the United States are limited. We examined colectomy rates during emergent admissions and elective ileal pouch anal anastomosis surgery (IPAA) rates. Methods: We analyzed data from the Nationwide Inpatient Sample (NIS) from 2000 through 2014. Inclusion criteria were admissions with a primary UC ICD-9 diagnosis code and age 18. Emergent cases were defined as admission through emergency room. We considered only the ICD-9 code for subtotal colectomy (45.8) within this group as the outcome variable. We defined a second cohort of UC patients admitted electively with an outcome variable of ICD-9 code for IPAA (35.05, 35.06) which was used as a surrogate measure of overall need for colectomy (final stage procedure for vast majority). Patient and hospital-level demographics were also analyzed. Temporal trends of colectomy were analyzed utilizing joinpoint regression analysis with calculation of annual percentage change (APC). Results: A total 470, 720 admissions were included over the study period. Colectomy rate among patients emergently admitted to the hospital significantly declined over 10 years (APC -7.35%, p<0.05) while the rate of elective IPAA remained stable (APC -0.21%, p=n.s.) (Figure 1). Emergent colectomy rates were higher in teaching hospitals. Colectomy rate among emergent admissions declined similarly across all demographics. However, IPAA rates were significantly higher among whites and those with private insurance (Figure 2). Conclusions: There has been a significant decline in emergent UC colectomy in the United States, likely due to more effective inpatient medical care. However, overall need for surgery appears to be stable given unchanged IPAA rates. This suggests a limited impact on overall surgery rates with a shift from emergent to elective procedures. There are disparities in IPAA rates based on race and insurance.